Consequences of post-weaning social isolation on anxiety behavior and related neural circuits in rodents - Lukkes, Jodi L.; Watt, Michael J.; Lowry, Christopher A.; Forster, Gina L. (Frontiers in Behavioral Neuroscience, 2009)
Exposure to adverse experiences in early-life is implicated in the later vulnerability to development of psychiatric disorders, including anxiety and affective disorders in humans. Adverse early-life experiences likely impart their long-term consequences on mental health by disrupting the normal development of neural systems involved in stress responses, emotional behavior and emotional states. Neural systems utilizing the neurotransmitters serotonin, dopamine and the neuropeptide corticotropin-releasing factor (CRF) are implicated in mediating emotive behaviors, and dysfunction of these neurochemical systems is associated with mood/anxiety disorders. These neural systems continue maturing until early or mid-adolescence in humans, thus alterations to their development are likely to contribute to the long-term consequences of adverse early-life experiences. A large body of literature suggests that post-weaning isolation rearing of rodents models the behavioral consequences of adverse early-life experiences in humans. Overall, the majority findings suggest that post-weaning social isolation that encompasses pre-adolescence produces long-lasting alterations to anxiety behavior, while measures of monoaminergic activity in various limbic regions during social isolation suggest alterations to dopamine and serotonin systems. The goal of this review is to evaluate and integrate findings from post-weaning social isolation studies specifically related to altered fear and anxiety behaviors and associated changes in neuroendocrine function and the activity of monoaminergic systems.